Analysis of Operating Temperature of the Polycrystalline Solar Cell - Vladimír GÁLL; Alexander MÉSZÁROS; Ján TKÁČ (Acta Electrotechnica et Informatica, 2017)
This work deals with the solar cells with orientation on the calculation of operating temperature of the polycrystalline solar cell, which is under actual load. Operating conditions have a significant effect on the efficiency of solar cells. In the summer with increasing temperature, the efficiency decreases. In the winter, efficiency and output voltage are rising. The operating temperature is determined by intensity of solar radiation, the types of materials used by construction and operating condition. The aim of this work was simplify of the calculation of operating temperature of solar cells. The result of this work is a derived equation that allows a more accurate and faster calculation this temperature with using Matlab software.